2015
DOI: 10.1080/10790268.2015.1109761
|View full text |Cite
|
Sign up to set email alerts
|

Is the pattern of dietary amino acids intake associated with serum lipid profile and blood pressure among individuals with spinal cord injury?

Abstract: Objective: The probable effect of dietary amino acids intake pattern on serum lipid profile and blood pressure (BP) have not yet been described among individuals with spinal cord injury (SCI). Design: Cross-sectional. Setting: Tertiary rehabilitation center. Participants: People with SCI referred to Brain and Spinal Cord Injury Research Center between 2011 and 2014. Outcome measures: Dietary intakes were assessed by recording consumed foods by 24-hour dietary recall interviews using Nutritionist IV 3.5.3 modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…However, several individual amino acids previously studied, documented contradictory findings on their associations with blood pressure. In the INTERMAP study, dietary phenylalanine, which was mostly supplied from plant sources showed no association with BP 9 , whereas phenylalanine and valine intakes were related to higher BP 8 , 21 similar to our first pattern, which is highly loaded with these amino acids. Tyrosine has been found to be associated with lower BP in cross sectional studies 4 , 7 , although, cohort studies show no association of tyrosine with BP 7 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, several individual amino acids previously studied, documented contradictory findings on their associations with blood pressure. In the INTERMAP study, dietary phenylalanine, which was mostly supplied from plant sources showed no association with BP 9 , whereas phenylalanine and valine intakes were related to higher BP 8 , 21 similar to our first pattern, which is highly loaded with these amino acids. Tyrosine has been found to be associated with lower BP in cross sectional studies 4 , 7 , although, cohort studies show no association of tyrosine with BP 7 .…”
Section: Discussionsupporting
confidence: 82%
“…Tyrosine has been found to be associated with lower BP in cross sectional studies 4 , 7 , although, cohort studies show no association of tyrosine with BP 7 . Although arginine as the precursor of NO had lowering effects on BP in trial studies 22 , 23 , conflicting results were reported by epidemiological ones 1 , 6 , 7 , 21 . These discrepancies in individual amino acid studies may be explained by the design, sample size, and different groups in these studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Lifestyle (including physical exercise and dietary intake) is universally known to play a vital role in the prevention of obesity and reduction of excessive body weight. Numerous studies have proved that there are associations between obesity and dietary amino acid intake in the general population [5, 6]. In our previous study, we found that a higher ratio of dietary branched-chain amino acids intake was inversely associated with the prevalence of overweight/obesity, abdominal obesity, postprandial glucose tolerance, and status of inflammation in young northern Chinese adults [7].…”
Section: Introductionmentioning
confidence: 99%